THE EFFECTIVENESS OF POP UP ADVERTISING ON SOCIAL MEDIA (CASE STUDY: FACEBOOK USER AT STUDENT COLLEGE FEB UNSRAT INSTITUTION) - Tambajong, Monica; Lapian, Joyce S.L.H.V.; Tumewu, Ferdinand J. (FEB Universitas Sam Ratulangi Manado, 2019)
A Pop up Advertising is a Pop up window used for advertising. When the program is initiated by some user action, such as a mouse click or a mouseover, a window containing an offer for some product or service appears in the foreground of the visual interface. The objective of this research is to know the effectiveness of pop up advertising on social media by analyzing the social media users perception. This research used Qualitative method with convenience sampling and took 35 respondent, in order to know more about pop up advertising from social media users experience. The result of this research is Pop up advertising can affect people buying interest to purchased product, also pop up advertising are effective to the all social media especially for facebook user who become a respondent in this research. Based on the result of interview the researcher recommended the company of pop up advertising can add more creativity content, reduce the time of pop advertising so that facebook users are not disturbed and also can affect more their buying interest. Keywords: pop up advertising, internet marketing, qualitative method, consumer perception